II - Physiological principles of acid-base balance: An integrative perspective - Domingos,Fernando (2015)
Normal human metabolism leads to the daily production of large amounts of volatile and non-volatile acids. The maintenance of the pH within physiological limits is a demanding task in which several mechanisms are involved. The most immediate answer comes from several physiological buffers that quickly neutralize pH deviations caused by the addition of strong acids or bases to the body. Bicarbonate/carbonic acid is the most important buffer pair of the extracellular milieu, but is chemically inefficient and depends on the continuous activity of the lung and kidney. Other physiological buffers have higher efficacy and are very important in the intracellular environment and renal tubules. The capacity of the various chemical buffers is kept by operating in an open system and by several controlling mechanisms. The lung is responsible for the elimination of the carbon dioxide (CO2) produced in the body. In metabolic disorders, respiratory adjustment of the elimination of CO2 prolongs the effect of the bicarbonate/carbonic acid buffer, but this process consumes bicarbonate. The kidney contributes to acid-base balance through several mechanisms: 1) controls the reabsorption of filtered bicarbonate; 2) regenerates bicarbonate consumed in buffer reactions; 3) eliminates non-volatile acids. Renal elimination of acid and bicarbonate regeneration is only possible due to the existence of several urinary buffers and to the ability of the kidneys to produce ammonia